EFFECT OF CAUSE-RELATED MARKETING CAMPAIGN ON BRAND IMAGE OF NON-ALCOHOLIC BEVERAGE COMPANIES IN NIGERIA - Onobrakpeya, Stanley Akpevwe; Bayagbon, Theresa Josh-Palmer (African Journal of Social and Behavioural Sciences, 2024)
The study explored the effect of cause-related marketing campaigns on the brand image of non-alcoholic beverage companies in Nigeria. The research design that was adopted for this study is the cross-sectional survey research design. The population of the study consists of customers of non-alcoholic beverage companies in Delta State Nigeria. The Cochran formula was used to determine the sample size of 384. The research employed the snowball sampling technique. The data for this study were basically obtained from the primary source using a structured questionnaire. The assessment of internal consistency for each construct was conducted to establish reliability of the research instrument. Data collected were analyzed using descriptive and inferential statistics. Findings showed that brand-cause fit, point-of-sale donations, and brand storytelling has significant positive effect on brand image. The study concluded that cause-related marketing campaign has significant positive effect on brand image. The study recommended amongst others that non-alcoholic beverage companies should meticulously select causes that align closely with their brand values and resonate authentically with their target audience.